Skin-To-Stone Distance On Computed Tomography KUB: An Independent Predictor Of Stone-Free Status After Shock Wave Lithotripsy - Mughal, Hina Hanif; Abdullah, Muhammad; Qadeer, Zeeshan; Riaz, Humaira; Shams, Nadia; Meraj, Lubna (Journal of Rawalpindi Medical College, 2025)
Objective: To evaluate SSD and other factors related to the characteristics of the patient and renal stone to predict the ESWL outcomes in patients with renal stones. Methods: A cross-sectional study was conducted on 90 patients undergoing ESWL for renal calculi. Pre-procedural CT scans were used to measure SSD, stone size, and CT attenuation values. Patients were followed post-ESWL by ultrasound and X-ray KUB to assess stone-free status. Correlation analysis, independent samples t-tests, chi-square tests, and binary logistic regression were used to assess associations between variables and treatment outcomes. Results: The mean value of SSD in our cases was 10 ± 0.72 cm, and 57.8% of patients had SSD ≤10 cm. A statistically significant difference in mean SSD was found between the group that was stone-free vs. the group with residual stones (p < 0.0001). Logistic regression confirmed SSD as an independent predictor of ESWL success (p < 0.00001), with increasing SSD significantly reducing the odds of being stone-free. Stratified analysis showed that 90% of patients with SSD ≤10 cm achieved stone-free status versus only 37.5% with SSD >10 cm (p < 0.0001). Conclusion: SSD is a statistically and clinically significant predictor of ESWL success. An SSD ≤10 cm is strongly associated with favorable outcomes. Given its simplicity, non-invasiveness, and predictive value, SSD should be incorporated into routine pre-ESWL evaluation to guide treatment planning and improve patient selection.